Resourcing resilience: social protection for HIV prevention amongst children and adolescents in Eastern and Southern Africa. Issue 2 (15th July 2016) - Toska, Elona; Gittings, Lesley; Hodes, Rebecca; Cluver, Lucie D; Govender, Kaymarlin; Chademana, K Emma; Gutiérrez, Vincent Evans
Abstract : Adolescents are the only age group with growing AIDS-related morbidity and mortality in Eastern and Southern Africa, making HIV prevention research among this population an urgent priority. Structural deprivations are key drivers of adolescent HIV infection in this region. Biomedical interventions must be combined with behavioural and social interventions to alleviate the socio-structural determinants of HIV infection. There is growing evidence that social protection has the potential to reduce the risk of HIV infection among children and adolescents. This research combined expert consultations with a rigorous review of academic and policy literature on the effectiveness of social protection for HIV prevention among children and adolescents, including prevention for those already HIV-positive. The study had three goals: (i) assess the evidence on the effectiveness of social protection for HIV prevention, (ii) consider key challenges to implementing social protection programmes that promote HIV prevention, and (iii) identify critical research gaps in social protection and HIV prevention, in Eastern and Southern Africa. Causal pathways of inequality, poverty, gender and HIV risk require flexible and responsive social protection mechanisms. Results confirmed that HIV-inclusive child-and adolescent-sensitive social protection has the potential to interrupt risk pathways to HIV infection and foster resilience. In particular, empirical evidence (literature and expert feedback) detailed the effectiveness of combination social protection particularly cash/in-kind components combined with "care" and "capability" among children and adolescents. Social protection programmes should be dynamic and flexible, and consider age, gender, HIV-related stigma, and context, including cultural norms, which offer opportunities to improve programmatic coverage, reach and uptake. Effective HIV prevention also requires integrated social protection policies, developed through strong national government ownership and leadership. Future research should explore which combinations of social protection work for sub-groups of children and adolescents, particularly those living with HIV.